The Characteristics of Bully Teenagers - PH, Livana; Kurian, Midhu; Ar Ruhimat, Imroati Istibsyaroh (Jurnal Ners Widya Husada, 2018)
TTeenagers have new value in accepting or not accepting members of various peer groups. One problem that is often faced by teenagers is related to peer rejection, namely the emergence of bullying behavior. The study aimed to determine the characteristics of teenagers who carry out bullying. This research was a quantitative research through descriptive analytic design. The sample of this research was 70 teenagers who have done bullying. The sampling was performed using random sampling method. The data were collected using a questionnaire. Research data were then analyzed univariately using central tendency and frequency distribution. The results showed that the average bully was 16 years old, with the youngest age was 15 years and the oldest was 17 years old, male, and class XI.Â Keywords: teenage characteristics, bullying